Site Suitability and Tolerance Limits of Trees, Shrubs and Grasses on Sodic Soils of Ganga-Yamuna Doab - Singh, Kalyan (Indian Forester, 1994)
Site suitability and tolerance limits of trees, shrubs and grasses to soil sodicity were evaluated under field conditions at Aligarh, Mathura, Agra and Mainpuri Districts (U.P.). Prosopis juliflora, Acacia leucophloea, Tamarix sp., Sporobolus marginatus Desmostochya bipinnata and Diplachne fusca were able to grow on sodic soils having average values of pH < 10, ESP < 60, Ece < 4dSm-1, CaCO3 < 10% and compact and indurated Kankar(CaCO3)/clay pan present beyond 1 m soil depth under rainfed conditions. Higher sodicity levels and Kankar pan within 1 m soil depth caused failure of vegetation. Acacia nilotica, Capparis zeylanica, Crotolaria medicaginea and Cynodon dectylon could grow successfully on soils which had maximum values of pH 9.5, ESP 50, Ece 4 dSm-1, CaCO3 5% under the conditions of deep ground water table and absence of compact and indurated Kankar pan in sub-soils. Mixed forest species like Terminalia arjuna, Azadirachla indica, Pongamia pinnta, Dalbergia sissoo, Albizia lebbek, Bulea monosperma, Phoenix sp., Calotropis procera, Prosopis cineraria, Cryptostegia grandiflora, Capparis decidua, Salvadora oleoides, Zizyphus mauritiana, Adhatoda vesica and Saccharum spontaneum were found to grow well on soils having lower sodicity levels (pH < 9, ESP < 35. Ece < 4 dSm1) and absence of clay/Kankar pan throughout the root zone 20-140 cm depth.